Understanding Alcoholism Through microRNA Signatures in Brains of Human Alcoholics - Mayfield, R. Dayne; Nunez, Yury O. (Frontiers in Genetics, 2012)
Advances in the fields of genomics and genetics in the last decade have identified a large number of genes that can potentially influence alcohol-drinking behavior in humans as well as animal models. Consequently, the task of identifying efficient molecular targets that could be used to develop effective therapeutics against the disease has become increasingly daunting. One of the reasons for this is the fact that each of the many alcohol-responsive genes only contributes a small effect to the overall mechanism and disease phenotype, as is characteristic of complex traits. Current research trends are hence shifting towards the analysis of gene networks rather than emphasizing individual genes. The discovery of microRNAs and their mechanisms of action on regulation of transcript level and protein translation have made evident the utility of these small non-coding RNA molecules that act as central coordinators of multiple cross-communicating cellular pathways. Cells exploit the fact that a single microRNA can target hundreds of mRNA transcripts and that a single mRNA transcript can be simultaneously targeted by distinct microRNAs, to ensure fine-tuned and/or redundant control over a large number of cellular functions. By the same token, we can use these properties of microRNAs to develop novel, targeted strategies to combat complex disorders. In this review, we will focus on recent discoveries of microRNA signatures in brain of human alcoholics supporting the hypothesis that changes in gene expression and regulation by microRNAs are responsible for long-term neuroadaptations occurring during development of alcoholism. We also discuss insights into the potential modulation of epigenetic regulators by a subset of microRNAs. Taken together, microRNA activity may be controlling many of the cellular mechanisms already known to be involved in the development of alcoholism, and suggests potential targets for the development of novel therapeutic interventions.